The inhibitory effect of some nanoparticles on biofilm formation of Streptococcus agalactiae - Haneen kadhum Abdul-Hamza; Ghaidaa Jihadi Mohammed (Al-Qadisiyah Journal of Pure Science, 2019)
:  Biofilm are a link between microorganisms in which germ cells stick together on living or non-living surfaces within a self-produced polymer